HECTOR’S HEROIC GLORY AGAINST THE GREEKS IN DAVID BENIOFF’S TROY MOVIE - KATYA DEWI HADIYANTI (The English Department, Faculty of Languages and Arts, Universitas Negeri Surabaya, 2013)
Judul skripsi ini adalah